2021
DOI: 10.21776/ub.jitode.2021.009.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Tourism SME’s Competitive Advantages through ICT Based Community : The Role of GenPI in Eastern Indonesia

Abstract: This article aims to describe the role of the tourism community in the utilization of ICT to market regional tourism destinations integrated with an increasing competitive advantage in Tourism SMEs. The perspective used is Community-Based Tourism Marketing (CBTM) and Resource-Based View (RBv) in the context of Collaborative Advantages (CA) towards the relationship of the tourism community with the regional tourism industry. This study was done in a qualitative manner using a case study approach. The data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…This research presents a certain unreadiness for the ICTs implementation in hotel organizations from the aspect of providing services, technological improvement and the ecosystem, which is demonstrated in the rejection of hypotheses H2, H4 and H5 at a significance level of 5% (H1 is accepted at 10%). In the research review, some authors emphasized the possible challenges and difficulties that arise in connection with the implementation of ICTs in hotels (Mihalic and Buhalis, 2013;Ghani et al 2022;Wynn and Jones 2022), but for the majority this is not the case because they consider that the application of certain technologies that are recognized as necessary for hotel business should be a necessity for improving the business of the entire ecosystem, raising the quality of technological equipment and developing innovations with regard to market dynamics (Domanski 2020;Infante-Moro et al 2021;Singgalen and Timisela 2021;Wahab et al 2022;Yorkulov et al 2022). In particular, if one looks at the groups of variables in the "Platform" and "Strategy" constructs, it can be concluded that in those areas of business that are key to the implementation of ICTs in the hotel, a sufficient level of readiness was not achieved according to the hypothesis test for those groups of variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research presents a certain unreadiness for the ICTs implementation in hotel organizations from the aspect of providing services, technological improvement and the ecosystem, which is demonstrated in the rejection of hypotheses H2, H4 and H5 at a significance level of 5% (H1 is accepted at 10%). In the research review, some authors emphasized the possible challenges and difficulties that arise in connection with the implementation of ICTs in hotels (Mihalic and Buhalis, 2013;Ghani et al 2022;Wynn and Jones 2022), but for the majority this is not the case because they consider that the application of certain technologies that are recognized as necessary for hotel business should be a necessity for improving the business of the entire ecosystem, raising the quality of technological equipment and developing innovations with regard to market dynamics (Domanski 2020;Infante-Moro et al 2021;Singgalen and Timisela 2021;Wahab et al 2022;Yorkulov et al 2022). In particular, if one looks at the groups of variables in the "Platform" and "Strategy" constructs, it can be concluded that in those areas of business that are key to the implementation of ICTs in the hotel, a sufficient level of readiness was not achieved according to the hypothesis test for those groups of variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, the foundation of the hospitality sector is a satisfied guest as a result of achieving excellence in meeting their demands and needs. Also, they pointed out it would be desirable that subsequent research should be stricter on a smaller geographical area such as hotel organizations in a certain region (Koo et al 2019;Mihalic and Buhalis 2013;Singgalen and Timisela 2021;Yorkulov et al 2022). On the other hand, some authors determine the importance of improving the integrated information system in hotels with the aim of better data processing, reporting and ultimately more efficient control in the organization through the examination of managers in IT sectors of hotels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, the identification of the researcher becomes a constraint because not all journals include the complete identity of the researcher, for example, Ahoren (2017). Or two or more different identities were found under one researcher, for instance: Herdiana (2020), wherein an affiliated article at the Cimahi School of Administrative Sciences (Sekolah Tinggi Ilmu Administrasi) (STIA), but in Google Scholar it was listed at the UIN Sunan Gunung Djati, Bandung, as Singgalen, which in his article stated Halmahera Peace Polytechnic but identity on Google Scholar verified at Atma Jaya Catholic University (Singgalen et al, 2018(Singgalen et al, , 2019Singgalen & Timisela, 2021). The authors assume this was due to switching affiliations or other technical issues.…”
Section: Methodsmentioning
confidence: 99%
“…Dalam beberapa kasus, identifikasi peneliti menjadi konstrain karena tidak semua jurnal mencantumkan identitas peneliti secara lengkap, contoh: Ahoren (2017). Atau ditemukan dua atau lebih identitas yang berbeda untuk satu peneliti, contoh: Herdiana (2020) dimana dalam artikel terafiliasi di Sekolah Tinggi Ilmu Administrasi (STIA) Cimahi namun dalam Google Scholar tercatat di institusi UIN Sunan Gunung Djati Bandung, selayaknya Singgalen yang dalam artikelnya mencantumkan Politeknik Perdamaian Halmahera namun identitas pada Google Scholar terverifikasi di Univeritas Katolik Atma Jaya (Singgalen et al, 2018(Singgalen et al, , 2019Singgalen & Timisela, 2021). Hal ini penulis asumsikan dikarenakan faktor pindah afiliasi atau persoalan teknis lain.…”
Section: Metodeunclassified
“…Topik masyarakat tidak hanya identik dengan wilayah geografis pedesaan saja, melainkan juga pulau, sebagaimana penulis temukan pada artikel Nurdin (2016) yang berupaya mengusulkan strategi pengembangan pariwisata berbasis masyarakat di Pulau Samalona, ataupun melihat peran masyarakat dalam memanfaatkan teknologi informasi, sebagaimana dikaji oleh Singgalen & Timisela (2021).…”
Section: Masyarakat Dan Partisipasi Masyarakatunclassified